SOCIAL PROBLEMS AND THEIR IMPACT ON COMMUNITY LIFE - Abdusamatova Odinaxon Abdusalom qizi (Scholar Express Journal, 2024)
This study aims to analyze environmental justice as a reflection of the issue of social justice. The authors analyzed the term “environmental justice,” which is directly related to “social justice.” The basis of environmental justice is the principles of a social organization projected onto the interaction between people and the environment
Keywords: violence; problems; juvenile crime; fellowship